Exploring impacts of the EED 420 science methods course on pre-service elementary teachers’ views regarding the nature of science - EunJin Bang (International Electronic Journal of Elementary Education, 2013)
This study explores the impact of a semester-long science methods course examining pre-service elementary teachers’ views on the nature of science (NOS). Also examined were NOS characteristics that pre-service teachers incorporated into their science lesson plans and peer teachings, during the course. Data used for this study were obtained from 21 pre-service teachers who participated in the pre/post card exchange game, pre/post VNOS interviews, 5E lesson plans, and peer teaching performances. The results of the study showed that some changes were made as a result of EED 420— such as starting to view science as a data-gathering experimental endeavor, rather than just a theorydriven endeavor. None of the groups explicitly designed or taught their lesson’s NOS aspects. The study posits that a mere one semester-long science method’s course is insufficient to adequately improve understanding of the NOS, and to establish a sufficiently robust desire in pre-service teachers for them to implement NOS into their lessons.